Sistema para la prestación del servicio de comidas para empresas en Quito - Cueva Rueda, Edgar Enrique (2007)
In this project we have analyzed the external environment to get enough information to know the overall situation is immersed our project on the "System for the provision of catering companies in Quito", the statistics provided by the INEC us has been crucial to analyze the perspective of the business and know that it is a good niche to be untapped; further analyze Porter's five forces, these parameters give us the guidelines of what to face when starting this type of business, the advantage of working with these theories is the ability to manage and adapt to our situation and establish strategies.